Development of a Practicum Guide on Static Electricity Using a Van de Graaff Generator for Students - Deni Sadly; Hamdi Akhsan (Postgraduate, University of Mataram, 2023)
This research aims to develop practical guidelines for the Van de Graaff Generator on Static Electricity for Students that are valid and practical. This research uses research and development research methods with the Rowntree development model. The Rowntree development model is product-focused, consisting of three stages: planning, development, and evaluation. At the evaluation stage using, Tessmer's formative evaluation, namely self-evaluation, expert review, one-to-one evaluation, and small group evaluation. This research collected data in two ways: walkthrough and student response questionnaires. The results of the two methods are then analyzed by finding the average percentage value and converted according to the predetermined category. Based on the results of the expert review, it was found that the average overall aspect was 90.80% which was categorized as very valid. At the one-to-one evaluation stage, an assessment of student responsiveness was obtained of 81.67%, categorized as practical. Furthermore, in the small group evaluation stage, the results of student responses were obtained by 87% in the very practical category. Thus, based on the results of the research, the Van de Graaff Generator (GVG) practicum guide on Static Electricity for Physics Education Students is very valid and practical.